1975
DOI: 10.1288/00005537-197504000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The vascular supply of the cervical skin with reference to incision planning d̊

Abstract: Wound breakdown, especially following preoperative radiotherapy, is a complication following neck surgery. The anatomy of the blood supply of the neck skin, which is an important factor in neck incision planning, was determined by silicone rubber injection studies. Some of the more common incisions interrupt the cervical blood supply, which descends from the facial and occipital arteries and ascends from the transverse cervical and suprascapular arteries, and this is discussed in relation to wound breakdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The MacFee incision is probably the one that heals the best because it is a bipedicled flap respecting the normal arrangement of the blood supply of the neck (Freeland et al, 1975). The flap gives access to all primary tumour sites but there is occasional difficulty in the patient with a short neck in separating the anterior end of the incision from a tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…The MacFee incision is probably the one that heals the best because it is a bipedicled flap respecting the normal arrangement of the blood supply of the neck (Freeland et al, 1975). The flap gives access to all primary tumour sites but there is occasional difficulty in the patient with a short neck in separating the anterior end of the incision from a tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Rabson et al reported that the blood supply of the neck skin anterior to the trapezius muscle descends from the facial and occipital arteries and ascends from the transverse cervical artery [ 11 ]. However, the midline of the neck skin where the incision was made is supplied from the branches of these major vessels running in a horizontal direction [ 12 ]. Due to the anatomical nature of the horizontal branching vessels, vertical incision of the anterior neck skin would comprise the cutaneous blood supply and tend to offer increased risk of development of pressure ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…These anastomoses remain intact during the neck dissection while the platysma is dissected from the skin (Ariyan, 1986). Even if the facial occipital and transverse cervical arteries are tied together, an alternative arterial supply will develop (Hetter, 1972;Freeland and Rogers, 1975). When considered from an oncological perspective in order to provide superficial lymphatic resection, the platysma can also be added to the specimen.…”
Section: Anatomymentioning
confidence: 99%
“…Despite these, one of the important drawbacks of this type of incision is that it destroys the neck's venous drainage from top to bottom. Unfortunately, this is a major cause of flap separation (Freeland and Rogers, 1975).…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation